Processing smoke plume products from the moderate resolution imaging spectroradiometer (MODIS) within a workflows environment - Chedzey, H.; Broomhall, M.; Garcia, R.; Fearns, P.; Lynch, Mervyn; King, E.; Wang, Z.; Smith, G. (2011)
A national web-based service is being designed to develop generic software tools to improve access to Australian satellite data. This remote sensing workflow, run in a High Performance Computing (HPC) environment, will allow end-users to easily access, process and analyse satellite data for their individual environmental research needs. Various products will be made available through the workflow including smoke plume products. The impact of smoke plumes on urban areas leads to respiratory problems in the population and, accordingly, building statistics on these events is of interest. Case studies will be presented to showcase the smoke detection methods being used and some of the forms of output available through the remote sensing workflows project.